Имунна недостатъчност и супресия на имунната система у деца с аутизъм - Трајковски, Владимир; Мирко Спироски (My University, 2002)
Etiology and pathogenesis of autism are still unknown. The disorder may be a constellation of multiple factors: neural, genetic, immune, environmental, and biochemical. The critically important job of fighting off infections falls to our immune system. Recent research by several scientists has shown that children with autism have serious abnormalities in this all- important system. Defects in the immune system may lead to overgrowth of the intestinal tract with organisms like yeast. The role of immunizations in causing immune deficiencies is very important. The aim of this article is to shown immunodeficient conditions in children with autism and possibility to their therapeutically solution. Autism is characterized with different types of immunodeficiency: myeloperoxidase deficiency, severe combined immunodeficiency disease, selective IgA deficiency, IgG subclass deficiency, and complement deficiency. Here are presented several types of immunotherapeutic methods such as: gamma globulin therapy, transfer factor therapy, treatment with IL-2, enzyme-potentiated desensitization, and two other kinds of pharmacotherapy of autism.
Immune deficiency and supression of immune system in children with autism
Keywords: autism, immune system, immunodeficiency; аутизъм, имунна система, имунодефицит